The Quality of Life of Suburbanities: A Case Study of the Gdańsk Agglomeration - Masik, Grzegorz (Bulletin of Geography. Socio-economic Series, 2010)
The article explains the meaning of the concept of ‘quality of life’, placing emphasis on its subjective dimension. As the concept is more and more discussed in the literature, the author intends to examine the satisfaction within public spaces for which local government is responsible. According to research made in Canada it is worth measuring not only satisfaction as such but also the importance of its constituent dynamics. Therefore, a survey made in the suburbs of the Gdańsk agglomeration asked respondents about their satisfaction with public transport, roads, environment, etc., including questions about the relative importance of such issues. The combination of satisfaction and importance provide the overall quality of life. At the end of the paper the author considers if there is a chance to improve the quality of life through a brief analysis of local governments expenditure.